Insights into the transfer of silicon isotopes into the sediment record - Panizzo, Virginia; Swann, George E.A.; Mackay, Anson W.; Vologina, Elena; Sturm, Michael; Pashley, Vanessa; Horstwood, Matthew S.A. (European Geosciences Union, 2016)
The first δ30Sidiatom data from lacustrine sediment traps are presented from Lake Baikal, Siberia. Data are compared with March surface water (upper 180 m) δ30SiDSi compositions for which a mean value of +2.28‰ ±  0.09 (95 % confidence) is derived. This value acts as the pre-diatom bloom baseline silicic acid isotopic composition of waters (δ30SiDSi initial). Open traps were deployed along the depth of the Lake Baikal south basin water column between 2012 and 2013. Diatom assemblages display a dominance ( > 85 %) of the spring/summer bloom species Synedra acus var radians, so that δ30Sidiatom compositions reflect predominantly spring/summer bloom utilisation. Diatoms were isolated from open traps and, in addition, from 3-monthly (sequencing) traps (May, July and August 2012) for δ30Sidiatom analyses. Mean δ30Sidiatom values for open traps are +1.23‰ ±  0.06 (at 95 % confidence and MSWD of 2.9, n = 10). Total dry mass sediment fluxes are highest in June 2012, which we attribute to the initial export of the dominant spring diatom bloom. We therefore argue that May δ30Sidiatom signatures (+0.67‰ ±  0.06, 2σ) when compared with mean upper water δ30SiDSi initial (e.g. pre-bloom) signatures can be used to provide a snapshot estimation of diatom uptake fractionation factors (ϵuptake) in Lake Baikal. A ϵuptake estimation of −1.61 ‰ is therefore derived, although we emphasise that synchronous monthly δ30SiDSi and δ30Sidiatom data would be needed to provide more robust estimations and therefore more rigorously test this, particularly when taking into consideration any progressive enrichment of the DSi pool as blooms persist. The near-constant δ30Sidiatom composition in open traps demonstrates the full preservation of the signal through the water column and thereby justifies the use and application of the technique in biogeochemical and palaeoenvironmental research. Data are finally compared with lake sediment core samples, collected from the south basin. Values of +1.30‰ ±  0.08 (2σ) and +1.43‰ ±  0.13 (2σ) were derived for cores BAIK13-1C (0.6–0.8 cm core depth) and at BAIK13-4F (0.2–0.4 cm core depth) respectively. Trap data highlight the absence of a fractionation factor associated with diatom dissolution (ϵdissolution) (particularly as Synedra acus var radians, the dominant taxa in the traps, is very susceptible to dissolution) down the water column and in the lake surface sediments, thus validating the application of δ30Sidiatom analyses in Lake Baikal and other freshwater systems, in palaeoreconstructions.